Cyprus Educational Leader Awards. Gold Award - "AVARIS -Emergency Medical Services Support System " - Kyriacou, Efthyvoulos C. (My University, 2026)
Cyprus Educational Leader Awards. Gold Award – Category Contribution to Society Title of Project «AVARIS – Emergency Medical Services Support System ». The award was for the system which supports the public Ambulance Call Center. June 2019.
Keywords: Service to society